A Nonoverlapping Domain Decomposition Method for Exterior 3-D Problem (Journal of Computational Mathematics, 2001)
In this paper, a nonoverlapping domain decomposition method, which is based on the natural boundary reduction (cf. [4,13,15]), is developed to solve the boundary value problem in exterior three-dimensional domain of general shape. Convergence analyses both for the exterior spherical domain and the general exterior domain are made. Some numerical examples are also provided to illustrate the method.
Keywords: Domain decomposition; D-N Algorithm; Exterior 3-D problem.